A Case of Unilateral Optic Neuropathy Following Influenza Vaccination. (4th July 2017) - Papke, David; McNussen, Patricia J.; Rasheed, Mehmoodur; Tsipursky, Michael S.; Labriola, Leanne T.
ABSTRACT: The influenza vaccination has greatly benefited public health, leading to significant reductions in flu season hospitalizations and deaths. However, with more widespread administration of this vaccine, it is expected that the absolute number of patients that present with unusual, adverse reactions will increase. Here, we report a case of a 55-year-old woman who developed a progressive optic neuropathy and severe visual loss associated with optic disc edema following influenza virus vaccination. Our patient also experienced other concurrent symptoms, including bilateral knee effusions, muscle spasms and a facial rash. The strong temporal connection between the vaccine administration and the development of sequelae suggests that the optic neuropathy was an adverse reaction. Furthermore, HLA typing of our patient revealed alleles that have been linked to autoimmune reactions, consistent with the notion that specific HLA alleles could be involved in the pathophysiology of these adverse reactions.